Refuges and risks: Evaluating the benefits of an expanded MPA network for mobile apex predators - Daly, Ryan; Smale, Malcolm J.; Singh, Sarika; Anders, Darrell; Shivji, Mahmood; Daly, Clare A. K.; Lea, James S. E.; Sousa, Lara L.; Wetherbee, Bradley M.; Fitzpatrick, Richard; Clarke, Christopher R.; Sheaves, Marcus; et al. (Diversity & distributions, 2018)
Aim: Concurrently, assessing the effectiveness of marine protected areas and evaluating the degree of risk from humans to key species provide valuable information that can be integrated into conservation management planning. Tiger sharks (Galeocerdo cuvier) are a wide-ranging ecologically important species subject to various threats. The aim of this study was to identify "hotspots" of tiger shark habitat use in relation to protected areas and potential risks from fishing. Location: Southwest Indian Ocean, east coast of South Africa and Mozambique. Methods: Satellite tags were fitted to 26 tiger sharks. A subset of 19 sharks with an average period at liberty of 197 (SD = 110) days were analysed using hotspot analysis to identify areas of core habitat use. The spatial and temporal overlap of significant hotspots with current and planned marine protected areas as well as risks from fishing and culling was then calculated. Results: There was a 5.97% spatial overlap between tiger shark hotspots and marine protected areas, which would increase significantly (p < .05) to 24.36% with the expansion of planned protected areas in South Africa and could be as high as 41.43% if Mozambique similarly expanded neighbouring protected area boundaries. Tiger sharks remained largely coastal, but only showed a spatial overlap of 5.12% with shark culling nets in South Africa. Only three sharks undertook open ocean migrations during which they were more likely to interact with longline fisheries in the region. Main conclusions: This study demonstrates how spatial information can be used to assess the overlap between marine protected areas and the core habitats of top marine predators and highlights how congruent transnational conservation management can improve the effectiveness of protected areas. Core habitat use of marine apex predators may also be indicative of productive habitats, and therefore, predators such as tiger sharks could act as surrogate species for identifying key habitats to prioritize for conservation planning.